Effect of Dilution Sampling on Particle Emissions and Size Distributions from a Modern Pellet Stove - Obaidullah, Md.; Bram, Svend; Ruyck, Jacques De (Journal of Renewable Energy and Smart Grid Technology, 2020)
A two stage partial flow dilution tunnel with the combination of a porous tube diluter (PRD) and an ejector diluter (ED) was used to examine the effect of dilution sampling on fine particle emissions and size distributions from an automatically fired small scale modern bottom feed pellet stove with a capacity of 5 kW. The combustion experiments were conducted using a state of the art instrument Electrical Low Pressure Impactor Plus (ELPI+), which measures fine particles in real time with a fast response time in a wide particle size range from 0.006 to 10 μm (micrometre) aerodynamic diameter. The particulate matter (PM) measurements were conducted according to the European standard EN 14785 for residential space heating appliances fired by wood pellets. Isokinetic sampling technique was not applied as the present study was emphasized on the very small particles, and results were limited to maximum PM2.5. Five combustion experiments (A, B, C, D and E) with different dilution ratios varied between 32.1 to 53.8 were conducted at a stove manufacturing plant in the southern part of Belgium. Measurements include the particle number emissions, particle mass of PM1 (size <1 μm) and PM2.5 (size <2.5 μm) emissions and particle size distributions. The experimental results showed that both particle number and mass emissions decreased with increasing dilution sampling. Both particle mass and number size distributions did not vary with increasing dilution sampling, but the maximum number of concentrations appeared at the particle size of about 125 nm (nanometre), while the maximum mass concentrations showed in the fine mode at the particle size of around 330 nm. The results obtained from this study provide new insights into the effects of dilution sampling on the measurements of fine particle emissions, providing important data for the ongoing research to define a standardized dilution sampling methodology for characterizing emissions from stationary combustion sources for fine particle emissions.